The influence of human Resource Competency and Budget Participation on the Reliability of Financial Reports with an Internal Control System as a Moderating Variable in the Jambi Regional Police in 2024 - Acong Setia Budi; Sri Rahayu; Muhammad Gowon (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of human resource competency and budget participation on the reliability of financial reports with the internal control system as a moderating variable in the Jambi Regional Police in 2024. The population in this study is Jambi Regional Police personnel who work in the financial sector consisting of 34 unit. Determining the sample in this research uses techniques total sampling where the entire population was used as a research sample consisting of 135 respondents. This research method uses descriptive quantitative methods. SEM-PLS was used to analyze this research data. The data used is primary data obtained from questionnaires distributed to respondents. The results of the research show that human resource competence has a significant effect on the reliability of financial reports and budget participation has no effect on the reliability of financial reports, while the internal control system as a moderating variable is able to influence on the variables of human resource competence and budget participation in increasing reliability of financial statements.